The link between interpersonal and interorganisational networking: The role of start-up members' achievement-related affect - Esperança, M. B.; Ferreira, A. I.; Leal, C. C.; Braun, T. (International Journal of Entrepreneurial Venturing, 2021)
This research examined the effect of start-up members' achievement-related affect on the link between interpersonal and interorganisational relationships (IORs). A sample of 469 employees from 135 German and 65 Portuguese start-ups (questionnaires) and a sample of 19 staff members of different Portuguese start-ups (interviews) participated in the current study. The regression results for the moderation model show that, for higher levels of achievement-related affect, interpersonal network building has a significant positive correlation with their perceived importance of IORs with non-investor stakeholders. Moreover, the indirect effect between interpersonal network maintenance and perceived importance of IORs was mediated by start-up members' achievement-related affect. This research sought to contribute to the interpersonal and interorganisational networking literatures. Findings suggest that motivations of achievement-related affect play a moderator or mediator role depending on the different profiles of the stakeholders (investors vs. non-investors).